High mortality in Nipah encephalitis is associated with presence of virus in cerebrospinal fluid - Chua, K.B.; Lam, S.K.; Tan, C.T.; Hooi, P.S.; Goh, K.J.; Chew, N.K.; Tan, K.S.; Kamarulzaman, A.; Wong, K.T. (2000)
During the outbreak of Nipah virus encephalitis in Malaysia, stored cerebrospinal fluid (CSF) samples from 84 patients (27 fatal and 57 nonfatal cases) were cultured for the virus. The virus was isolated from 17 fatal cases and I nonfatal case. There were significant associations between CSF virus isolation and mortality as well as clinical features associated with poor prognosis. In addition, there was a positive linear correlation of CSF virus isolation with age. There was no significant association between CSF virus isolation and the character of the CSF, presence of Nipah-specific antibody in the serum or CSF, duration of illness before collection of samples, or sex or ethnicity of the patients. This study suggests that high vital replication in the central nervous system may be an important factor for high mortality.